Articulating arts and intercultural education: static and dynamic views of language teaching at school. (3rd July 2020) - Stratilaki-Klein, Sofia
ABSTRACT: In this contribution, we argue that consideration should be given to the implications of a holistic approach to language acquisition as a fundamental part of plurilingual and pluricultural education serving several aims of a knowledge-based and innovative learning through metalinguistic knowledge, well beyond developing communicative competence in the language of schooling. By analysing discourse data, we examine to what extent the success of such a plurilingual education is dependent on how the notion of plurilingual speaker is presented, represented by visual images, taught, developed as well as broadly discussed (and understood) among the school community.